Analisis Transparansi Dan Akuntabilitas Keuangan Alokasi Dana Desa (ADD) Di Kecamatan Sekongkang - Alya Ambarwati; Baiq Kisnawati; Rusli Amrul (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
Transparency and accountability from the government become a reference in financial management, especially in ADD. As legal community unit that has the authority to regulate and manage the interests of its own community in carrying out its duties, village requires sufficient funds. Accountability will be more effective if it is supported by an accounting system that produces accurate, reliable, timely, and accountable information. purpose of this research is to analyse the transparency and accountability of the financial allocation of village funds in the Sekongkang. The research used is descriptive qualitative. Data collection techniques are carried out by triangulation, data analysis tends to be inductive / qualitative, and the results of leatherative research emphasize more on meaning than generalization. Planning carried out in realising the Village Fund Allocation has been carried out well. The realisation of ADD, namely the use of Village Funds, is prioritised to finance development, community development aimed at improving the welfare of the village community, improving the quality human life and reducing poverty as outlined RKPDes. As well as the accountability provided has been done well by always reporting to stakeholders and the community with the results of the realisation of ADD